Plant Virology Protocols From Virus Isolation to Transgenic Resistance - Foster, Gary D.; Taylor, Sally; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1998)
Plant Virology Protocols offers for the first time a comprehensive collection of state-of-the-art techniques for generating transgenic plants that are resistant to plant viruses via the cloning and expression of the coat protein gene. Its unfailingly reproducible methods, perfected by hands-on masters, cover the entire process from virus isolation, RNA extraction, and cloning coat protein genes, to the introduction of the coat protein gene into the plant genome and the testing of transgenic plants for resistance. Methods for testing for transformation by PCR and Southern blotting, the detection of RNA transcripts by Northern blotting, and the production of protein by Western analysis are provided, as are methods for challenging the transgenic plants produced and for detecting and measuring the levels of virus. The authoritative contributors also discuss the history and mechanisms of coat protein-mediated protection and the key ethical issues surrounding transgenic technology. Unprecedented in its comprehensiveness and its many time-proven methods, Plant Virology Protocols is certain to become the authoritative standard reference for plant scientists who want to tap the enormous benefits this technology has to offer.
to Plant Virology -- to Classical Crossprotection -- History of Coat Protein-Mediated Protection -- Virus Isolation, RNA Extraction, and Location of Coat Protein Genes -- Geminivirus Isolation and DNA Extraction -- Caulimovirus Isolation and DNA Extraction -- Reovirus Isolation and RNA Extraction -- Procedures for Plant Rhabdovirus Purification, Polyribosome Isolation, and Replicase Extraction -- Hordeivirus Isolation and RNA Extraction -- Furovirus Isolation and RNA Extraction -- Tobravirus Isolation and RNA Extraction -- Tobamovirus Isolation and RNA Extraction -- Potexvirus Isolation and RNA Extraction -- Carlavirus Isolation and RNA Extraction -- Potyvirus Isolation and RNA Extraction -- Trichovirus Isolation and RNA Extraction -- Ilarvirus Isolation and RNA Extraction -- Bromovirus Isolation and RNA Extraction -- Cucumovirus Isolation and RNA Extraction -- Nepovirus Isolation and RNA Extraction -- Comovirus Isolation and RNA Extraction -- Carmovirus Isolation and RNA Extraction -- Tymovirus Isolation and Genomic RNA Extraction -- Tombusvirus Isolation and RNA Extraction -- Luteovirus Isolation and RNA Extraction -- Cloning of Coat Protein Genes -- RNA Analysis -- RNA Fractionation by Density Gradient Centrifugation -- cDNA Library Construction for the Lambda ZAP®-Based Vectors -- PCR Cloning of Coat Protein Genes -- Antibody Production -- Expression Library Screening -- In Vitro Transcription and Translation -- Analysis of Coat Protein Expression Cassettes in Protoplasts -- DNA Sequencing -- Computer Analysis of Amino Acid Sequences -- Plant Transformation and Primary Analysis -- Preparation of Coat Protein-Containing Binary Vectors for Use in Agrobacterium-Mediated Transformation -- Potato Transformation -- Transformation of Tomato -- Tobacco Transformation -- Genetic Transformation of Wheat -- Production of Transgenic Rice (Oryza sativa subspecies japonica cv. Taipei 309) -- Molecular Analysis of Transgenic Rice -- PCR Analysis of Transgenic Tobacco Plants -- Southern Analysis of Transgenic Tobacco Plants -- Detection and Quantification of Transcript RNA in Transgenic Plants Using Digoxigenin-Labeled cDNA Probes -- Western Analysis of Transgenic Plants -- Evaluation of Resistance -- Assaying Levels of Plant Virus by ELISA -- Detection of Plant RNA Viruses by Nonisotopic Dot-Blot Hybridization -- Detection and Quantification of Plant Viruses by PCR -- Assaying Levels of Virus with Local Lesion Hosts -- Field Testing Resistance of Transgenic Plants -- Agronomic Performance of Transgenic Plants -- Mechanisms of Resistance -- Mechanisms of Resistance -- Mechanisms of RNA-Mediated Resistance to Plant Viruses -- Detection of Risks Associated with Coat Protein Transgenics -- Potential Benefits of the Transgenic Control of Plant Viruses in the United Kingdom.
Keywords: Plant science; Botany; Plant Sciences